Advances in Piezo‐Phototronic Effect Enhanced Photocatalysis and Photoelectrocatalysis. Issue 15 (28th February 2020) - Pan, Lun; Sun, Shangcong; Chen, Ying; Wang, Peihong; Wang, Jiyu; Zhang, Xiangwen; Zou, Ji‐Jun; Wang, Zhong Lin
Abstract: Direct conversion of solar light into chemical energy by means of photocatalysis or photoelectrocatalysis is currently a point of focus for sustainable energy development and environmental remediation. However, its current efficiency is still far from satisfying, suffering especially from severe charge recombination. To solve this problem, the piezo‐phototronic effect has emerged as one of the most effective strategies for photo(electro)catalysis. Through the integration of piezoelectricity, photoexcitation, and semiconductor properties, the built‐in electric field by mechanical stimulation induced polarization can serve as a flexible autovalve to modulate the charge‐transfer pathway and facilitate carrier separation both in the bulk phase and at the surfaces of semiconductors. This review focuses on illustrating the trends and impacts of research based on piezo‐enhanced photocatalytic reactions. The fundamental mechanisms of piezo‐phototronics modulated band bending and charge migration are highlighted. Through comparing and classifying different categories of piezo‐photocatalysts (like the typical ZnO, MoS2, and BaTiO3 ), the recent advances in polarization‐promoted photo(electro)catalytic processes involving water splitting and pollutant degradation are overviewed. Meanwhile the optimization methods to promote their catalytic activities are described. Finally, the outlook for future development of polarization‐enhanced strategies is presented. Abstract : The piezo‐phototronic effect enables the engineering of charge‐carrier characteristics at both heterojunction interfaces and the bulk phase, and provides a driving force for the transport of photoinduced charges in specific directions. This review focuses on the advanced polarization‐promoted processes involving water splitting and pollutant degradation.